2022
DOI: 10.3390/educsci12030208
|View full text |Cite
|
Sign up to set email alerts
|

Usability of Memes and Humorous Resources in Virtual Learning Environments

Abstract: This research consists of a quantitative analysis of the perspective of a group of university professors from different areas of knowledge and from 19 different Latin American countries on the use of humor and memes in virtual learning environments (VLEs) in higher education. The data have been obtained from an own-design survey, and the answers have been analyzed in a descriptive and inferential way with the aim of knowing the opinion of the 401 participants (professors) about the didactic effectiveness of hu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 56 publications
0
6
0
3
Order By: Relevance
“…Regarding the sharing of materials, professors have probably found themselves with the advantage that there are content repositories, such as YouTube ® [31], messaging platforms, such as WhatsApp ® [34], and social networks, such as Instagram ® [31] or TikTok ® [34], which were already used by young people, although not for educational purposes [21][22][23][24][25]. Among other things, the use of these types of platforms has allowed professors to incorporate innovative methodological recourses in their classes, such as humorous resources [101]. All this has undoubtedly facilitated the integration of ICT tools in academic activities, which may explain why their use has increased during the pandemic to a greater extent than other tools (Figure 5).…”
Section: Discussionmentioning
confidence: 99%
“…Regarding the sharing of materials, professors have probably found themselves with the advantage that there are content repositories, such as YouTube ® [31], messaging platforms, such as WhatsApp ® [34], and social networks, such as Instagram ® [31] or TikTok ® [34], which were already used by young people, although not for educational purposes [21][22][23][24][25]. Among other things, the use of these types of platforms has allowed professors to incorporate innovative methodological recourses in their classes, such as humorous resources [101]. All this has undoubtedly facilitated the integration of ICT tools in academic activities, which may explain why their use has increased during the pandemic to a greater extent than other tools (Figure 5).…”
Section: Discussionmentioning
confidence: 99%
“…Common themes within these posts included the difficulties students were facing with learning anatomy content and study aids to help students remember anatomy content. Research has previously established the importance of humor and its ability to engage students, attract students' attention and improve fact recall particularly in online learning environments (Erdoğdu & Çakıroğlu, 2021; Antón‐Sancho et al., 2022). The rising number of humor‐based posts seen between 2019 and 2021 may additionally be revealing of the demand for more positive morale boosting posts over the course of the pandemic perhaps due to increasing concerns medical students had over interrupted studies (Alsoufi et al., 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Yet, several studies have revealed that language learners may face challenges when using memes, which may limit their usability in language classrooms. Antón-Sancho et al (2022) found that the usability of memes in virtual environments in higher education was intermediate due to several reasons: the challenges of achieving some objectives using humorous resources as a method; ethical issues (e.g., the risk of offending or insulting a particular social group); and the risk of misusing memes as a humorous resource instead of an effective learning tool. Romero and Bobkina (2021) noted that while language learners can decode the literal or descriptive meanings of memes, they may face difficulties interpreting the cultural meanings of the text and identifying their supposed intentions.…”
Section: Humor In Language Classroomsmentioning
confidence: 99%
“…Step 5: Discussion All of the nine reviewed articles have found memes to be significantly beneficial if implemented appropriately. Aside from being a fun and innovative way to spark moments of laughter in the classroom, the studies have revealed positive results and attitudes toward memes among instructors and students (Al Rashdi, 2020;Antón-Sancho, et al, 2022;de OLIVEIRA, 2022;Kayali & Altuntaş, 2021;Purnama, et al, 2017;Purnama, 2017;Romero & Bobkina, 2017;Romero & Bobkina, 2021;Zakharova, 2021). The major findings from the systematic review are summarized as follows and answer the research question: What is the effect of meme-related pedagogical activities in EFL/ESL classrooms?…”
Section: Antón-sancho Et Al (2022)mentioning
confidence: 99%
See 1 more Smart Citation